A global analysis of aerial displays in passerines revealed an effect of habitat, mating system and migratory traits - Mikula, Peter; Toszogyova, Anna; Albrecht, Tomáš (Proceedings. Biological sciences, 2022)
Aerial displaying is a flamboyant part of the sexual behaviour of several volant animal groups, including birds. Nevertheless, little attention has been focused on identifying correlates of large-scale diversity in this trait. In this study, we scored the presence and absence of aerial displays in males of 1732 species of passerine birds (Passeriformes) and employed Bayesian phylogenetically informed mixed models to test for associations between aerial displays and a set of life-history and environmental predictors. Our multi-variate models revealed that species with males that perform aerial displays inhabited open rather than closed (forested) habitats. These species also exhibited higher levels of polygyny, had more elongated wings, migrated over longer distances and bred at higher latitudes. When we included species where the sexual function of displays has not been explicitly described but is likely to occur, we found that aerial displaying was also associated with smaller body size and increased male plumage coloration. Our results suggest that both sexual selection and natural selection have been important sources of selection on aerial displays in passerines.
Keywords: Passeriformes; zvířata; sensory drive hypothesis; motor performance; Phenotype; gestural displays; visual ornaments; mužské pohlaví; ekosystém; signalling traits; phylogenetic comparative analysis; Ecosystem; fenotyp; Reproduction; rozmnožování; Bayes Theorem; Animals; Male; Bayesova věta